Aloysia citrodora extract as a chemopreventive agent against HPV16-induced lesions: findings from K14-HPV16 mice - Medeiros-Fonseca, Beatriz (2024)
Aim: Aloysia citrodora has a long history of traditional use in treating various ailments. This study evaluated the in vivo chemopreventive efficacy and systemic toxicity of an extract of A. citrodora in a transgenic mouse model of HPV16 (human papillomavirus type 16)-induced cancer. Methods: The experiment involved six groups (n = 5): group 1 (G1, wild-type (WT), water), group 2 (G2, HPV, water), group 3 (G3, WT, 0.013 g/mL), group 4 (G4, HPV, 0.006 g/mL), group 5 (G5, HPV, 0.008 g/mL), and group 6 (G6, HPV, 0.013 g/mL). Throughout the assay, humane endpoints, body weight, food, and water consumption were recorded weekly. The internal organs and skin of the mice were collected for analysis after they were sacrificed. Toxicological parameters that were studied included hematological and biochemical blood markers, splenic and hepatic histology, and hepatic oxidative stress. Results: A. citrodora extract seems to reduce the incidence of dysplastic and in situ carcinoma skin lesions induced by HPV16 in this model, suggesting that dietary supplementation with concentrations of 0.008 g/mL and 0.013 g/mL may have beneficial chemopreventive effects. Conclusions: The extract did not induce any concentration-dependent toxicological effects on any of the parameters included in the study, indicating a favorable toxicological profile under these experimental conditions.